2018
DOI: 10.5114/ceh.2018.80122
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolic disorders in the pathogenesis of intrahepatic cholestasis of pregnancy

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disorder which typically commences in the late second or third trimester and resolves within 48 hours after delivery. It is characterized by mild to severe pruritus, without any specific dermatologic features, elevated liver enzymes and increased serum bile acids (BA). The etiology of ICP is still not completely explicit. Pathogenesis includes a combination of hormonal and environmental factors superimposing on a genetic predisposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 49 publications
1
27
0
1
Order By: Relevance
“…This correlation could be the result of observational bias as closer observation of women who develop one disease may lead to a higher chance of detecting another disease in these women; however, we find it more plausible that there is a shared etiology linking these diseases. Previous studies have suggested a common metabolic syndrome, which has also been linked with obesity, artificial reproduction treatment, gestational diabetes, preeclampsia, and age, all of which are associated with ICP in our study as well 15,16 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This correlation could be the result of observational bias as closer observation of women who develop one disease may lead to a higher chance of detecting another disease in these women; however, we find it more plausible that there is a shared etiology linking these diseases. Previous studies have suggested a common metabolic syndrome, which has also been linked with obesity, artificial reproduction treatment, gestational diabetes, preeclampsia, and age, all of which are associated with ICP in our study as well 15,16 …”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have suggested a common metabolic syndrome, which has also been linked with obesity, artificial reproduction treatment, gestational diabetes, preeclampsia, and age, all of which are associated with ICP in our study as well. 15,16 Because of the reported increased risks of fetal demise, various guidelines advocate active management by intense surveillance in pregnancy and early delivery. From this study-and the results of the Swedish study in particular-we confirm that mild ICP with no concurrent preeclampsia or diabetes implies a low risk of stillbirth and asphyxia; perhaps lower than in the general pregnant population.…”
Section: Discussionmentioning
confidence: 99%
“…In Doppler average comparisons conducted according to gestation weeks, it was observed that there was no correlation. In the literature, there are publications asserting that meconium causes acute umbilical vein construction and decrease in umbilical flow [18]. And yet, we could not establish any value in this regard with Doppler data we obtained.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, other studies reported contradictory values suggesting a wide metabolic disparity between species, rodent strain, and time of damage exposure [38,39]. In addition, it has been established that intrahepatic cholestasis of pregnancy (ICP) and PBC are associated with impaired metabolic profile, including glucose intolerance and dyslipidemia [33,34]. Our analysis showed few data on metabolic parameters for BDL (Table 3).…”
Section: Discussionmentioning
confidence: 65%
“…Despite Sprague Dawley was developed from Wistar strain, data show that Wistar strain is prone for metabolic impairments [32]. This should be relevant in taking into account the metabolic component of cholestasis [33,34].…”
Section: Discussionmentioning
confidence: 99%